Electrospun magnetoactive hybrid P(VDF-TrFE) scaffolds heavily loaded with citric-acid-modified magnetite nanoparticles - Botvin V. V. Vladimir Viktorovich; Shlapakova L. E. Lada Evgenievna; Mukhortova Yu. R. Yulia Ruslanovna; Vagner D. V. Dmitry Viktorovich; Gerasimov E. Yu. Evgeny; Romanyuk K. N. Konstantin Nikolaevich; Surmeneva M. A. Maria Alexandrovna; Kholkin A. L. Andrei Leonidovich; Surmenev R. A. Roman Anatolievich (2024, 2024)
Title screen